TALENT MANAGEMENT AS A CRITICAL COMPONENT OF HUMAN RESOURCE DEVELOPMENT IN THE ERA OF SOCIETY 5.0 - Purnantara, I Made Hadi; Darma, Gede; Maradona, Agus (Faculty of Economic and Business, University of Pasundan, 2026)
The emergence of Society 5.0 redefines the strategic role of human resources within human-centered digital ecosystems, requiring organizations to realign talent development with evolving competency demands. Although talent management has been widely discussed in digital transformation literature, limited research systematically integrates its competency dimensions within the Society 5.0 framework. This study employs a Systematic Literature Review (SLR) analyzing 24 peer-reviewed journal articles through structured identification, screening, and thematic synthesis. The findings reveal three interrelated themes: (1) the repositioning of human resources as the core of human-centered digital transformation, (2) talent management as a strategic alignment mechanism linking digital strategy and human capability, and (3) six interdependent competency dimensions: leadership capability, language proficiency, digital literacy, writing and communication skills, innovation and creativity, and emotional intelligence. This study offers a structured competency-based framework positioning talent management as a transformation architecture aligned with Society 5.0 principles.